New Network Architectures The Path to the Future Internet - Tronco, Tania.; Tronco, Tania. (Studies in Computational Intelligence,, 2010)
"Future Internet" is a worldwide hot topic. The Internet has become a critical infrastructure for business development and social interactions. However, the immense growth of the Internet has resulted in additional stresses on its architecture, resulting in a network difficult to monitor, understand, and manage due to its huge scale in terms of connected devices and actors (end users, content providers, equipment vendors, etc). This book presents and discusses the ongoing initiatives and experimental facilities for the creation of new Future Internet Architectures using alternative approaches like Clean Slate and Incremental improvements: It considers several possible internet network use scenarios that include seamless mobility, ad hoc networks, sensor networks, internet of things and new paradigms like content and user centric networks.